Pengaruh Kualitas Pelayanan dan Kepercayaan Terhadap Loyalitas Konsumen dengan Kepuasan Sebagai Variabel Mediasi (Studi pada Ideo Photography di Semarang) - Kristian Agma Lambang Wibowo; MY. Dwi Hayu Agustini (JEMAP, 2020)
The purpose of this study was to determine the effect of service quality and trust on consumer loyalty with satisfaction as a mediating variable on Ideo Photography in Semarang. The population of this study is consumers who use Ideo Photography services, with unknown number of consumers. The sample of this study was 96 respondents. The sampling technique is purposive sampling. Data collection is done by distributing questionnaires through Google form. Data analysis techniques used multiple linear regression analysis. The results showed that: service quality significantly affects customer satisfaction, trust influences customer satisfaction, customer satisfaction affects customer loyalty. Service quality influences customer loyalty. Trust influences consumer loyalty. Service quality influences customer loyalty through customer satisfaction. Trust influences customer loyalty through customer satisfaction.